FEASIBILITY ANALYSIS OF FISH HANDLING PRACTICES IN THE SABILULUNGAN MODERN FISH MARKET - Wulandari, Tri; Poernomo, Achmad; Irianto, Hari Eko (Universitas Mataram, 2025)
In 2018 the Ministry of Maritime Affairs and Fisheries built the Sabilulungan modern fish market in Bandung Regency. This modern fish market was built the main aim of eliminating the public’s image of fish markets as dirty, muddy, smelly, and dirty. This research was conducted to determine the appropriateness of fish handling methods in modern fish markets. Analysis of the feasibility of fish handling methods is carried out by referring to the fish handling practice implementation checklist regulated by the Ministry of Maritime Affairs and Fisheries for supplier units. The assessment is modified with the Guttman scale and the finalo result will conclude the feasibility of the treatment method in the form of a percentage. The research result stated that the method of fish handling in modern fish market sabilulungan was not feasible with a feasibility value of 40.4%. It is recommended that modern fish market sabilulungan immediately create a management standard operating procedure, complete a documentation system, be firm in developing traders, appoint a special officer to be responsible for quality, complete and recognize facilities and infrastructure according to requirement, provide counseling regarding the principles of hygienic sanitation and training on good fish handling methods.